The Relationship Between Pregnant Women's Knowledge of Pregnancy Emergencies and Compliance with Ante Natal Care (ANC) Checkups - Prana Citra; Surmiasih Surmiasih (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Pregnancy emergencies are pregnant women who may experience complications during their pregnancy. Lampung Province reported 105 maternal deaths (75.15%), while South Lampung reported 5 maternal deaths in 2023. ANC coverage in South Lampung is 81.5%. The lowest achievement is at the Merbau Mataram Community Health Center with an achievement of 43.8%. Puspose: To determine the relationship between pregnant women's knowledge about pregnancy emergencies and compliance with antenatal care (ANC) in Mekar Jaya Village, Merbau Mataram Community Health Center. Method: This study is quantitative with a cross-sectional approach. The study population consists of all pregnant women in their first to third trimesters in Mekar Jaya Village, Merbau Mataram Community Health Center working area, totaling 67 respondents. The sampling technique used total sampling. Data collection was conducted using questionnaires on maternal emergencies and ANC compliance. Data analysis was performed using the chi-square test. Results: The results showed that the frequency distribution of ANC compliance indicated that most patients (61.2%) were non-compliant. Most (58.2%) had poor knowledge dan p-value of 0.001. Conclusion: There was a relationship between pregnant women's knowledge about pregnancy emergencies and their compliance with antenatal care (ANC) in Mekar Jaya Village, Merbau Mataram Health Center. It is hoped that pregnant women will reduce pregnancy emergencies so that they are more compliant in attending antenatal care visits, with a minimum of 6 visits (2 in the first trimester, 1 in the second trimester, and 3 in the third trimester).